THE EFFECT OF IMPLEMENTING CURRICULUM 2013 ON THE CHARACTER BUILDING OF LEARNERS AT MTS NEGERI 1 MAKASSAR CITY (International Conference on Social and Islamic Studies, 2022)
This study aims to describe the implementation of the 2013 curriculum, describe the formation of student character and analyze the influence of Curriculum 2013implementation on student character formation. This research is a quantitative research. The sample used by researchers in this study were class VII students at MTs Negeri 1 Makassar City, when the research was carried out on September 27 2021 – October 6 2021. The data collection method used was a questionnaire/questionnaire and documentation. The total population in this study amounted to 400 class VII students at MTs Negeri 1 Makassar City and the sample in this study was 60 respondents. The data analysis technique used is descriptive statistical techniques and inferential analysis techniques using the Product Moment Correlation formula. This study used a quantitative ex post facto approach and obtained results on the implementation of the curriculum in the moderate category, namely 98.33% based on an analysis of the results of a questionnaire from 60 respondents. The formation of the character of students is also in the medium category, namely 100% obtained from questionnaire data from 60 respondents. Based on the results of testing the hypothesis using the product moment correlation formula which shows that rxy = 0.678 with a significant level of 5% of 0.266. This shows that rcount 0.678 > rtable 0.266. Then there is a significant influence between the implementation of Curriculum 2013on the formation of the character of students at MTs Negeri 1 Makassar City as evidenced through the results of an analysis of the questionnaire where the significance value of tcount is 7.025 > ttable 1.671 at a significance level of 5%, so this shows that there is an influence between the application Curriculum 2013on the formation of the character of students at MTs Negeri 1 Makassar City.